Transisi Emosional Awal Pesantren di SMP Ma’had Hawa Lita’liml Qur’an - Fadhilah Aida Rasyid; Hamam (Jurnal Dirosah Islamiyah, 2025)
The purpose of this study is to determine the occurrence of the Early Emotional Transition of Islamic Boarding Schools at SMP Ma'had Hawa Lita'limil Qur'an Cipanas. see and know. The type of research used in this study is quantitative research, and the method used is a survey method used to obtain data that occurred in the past or present, about beliefs, opinions, characteristics, behavior, relationship variables and to test several hypotheses about sociological and psychological variables from the sample.